Chemotaxis without Conventional Two-Component System, Based on Cell Polarity and Aerobic Conditions in Helicity-Switching Swimming of Spiroplasma eriocheiris - Liu, Peng; Zheng, Huajun; Meng, Qingguo; Terahara, Natsuho; Gu, Wei; Wang, Shengyue; Zhao, Guoping; Nakane, Daisuke; Wang, Wen; Miyata, Makoto (Frontiers in Microbiology, 2017)
Spiroplasma eriocheiris is a pathogen that causes mass mortality in Chinese mitten crab, Eriocheir sinensis. S. eriocheiris causes tremor disease and infects almost all of the artificial breeding crustaceans, resulting in disastrous effects on the aquaculture economy in China. S. eriocheiris is a wall-less helical bacterium, measuring 2.0 to 10.0 µm long, and can swim up to 5 µm per second in a viscous medium without flagella by switching the cell helicity at a kink traveling from the front to the tail. In this study, we showed that S. eriocheiris performs chemotaxis without the conventional two-component system, a system commonly found in bacterial chemotaxis. The chemotaxis of S. eriocheiris was observed more clearly when the cells were cultivated under anaerobic conditions. The cells were polarized as evidenced by a tip structure, swimming in the direction of the tip, and were shown to reverse their swimming direction in response to attractants. Triton X-100 treatment revealed the internal structure, a dumbbell-shaped core in the tip that is connected by a flat ribbon, which traces the shortest line in the helical cell shape from the tip to the other pole. Sixteen proteins were identified as the components of the internal structure by mass spectrometry, including Fibril protein and four types of MreB proteins.